Early discontinuation and results reporting of robot-assisted surgery studies registered on ClinicalTrials.gov: a research on research study - Liang Du; Jin Huang; Youlin Long; Tengyue Hu; Zixin Yang; Liqin Liu; Yifei Lin (BMJ Open)
Objectives In this study, we aimed to investigate the characteristics of robot-assisted surgery studies registered on ClinicalTrials.gov and identify factors associated with early trial discontinuation and timely results reporting.Design We searched ClinicalTrials.gov to identify interventional studies on robot-assisted surgery on 24 May 2021. All structured information of the potential studies was downloaded and reviewed. A descriptive analysis was performed. Logistic and Cox regression analyses were respectively performed to determine the significance of the association of study characteristics with results reporting and early discontinuation.Results A total of 529 interventional studies on robot-assisted surgery were included, with 45 studies reporting results and 54 studies being stopped early. Of the 289 due studies, only 45 (16%) had submitted their results, and only 6 (2%) had submitted their results within the 1-year deadline. Funding source was associated with results reporting: academic funded were 63% less likely than industry to report results (OR=0.37, 95% CI: 0.16 to 0.83, p=0.02). Studies related to device feasibility were associated with greater risk of early discontinuation compared to treatment-related studies (HR=2.30, 95% CI: 1.08 to 4.89, p=0.03). Surprisingly, National Institutes of Health-funded studies were at greater hazard of discontinuation compared to industry-funded studies (HR=3.30, 95% CI: 1.09 to 10.00, p=0.04).Conclusions There was poor compliance with results reporting requirements for robot-assisted surgical studies. It is important that investigators remain informed about the regulatory requirements, and should be helped to develop a sense of responsibility for reporting results. Also, they need to ensure the careful design of the study protocol and adequate resources to reduce the risk of early discontinuation.